The Effect of the Good Behavior Game (GBG) on Adolescents' Knowledge of Sexual Violence Prevention - Intan Fazrin; Dina Yulia Puspita; Zainal Andy Saputra; Arina Chusnatayaini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Many studies have shown that education can improve adolescents' knowledge about sexual violence prevention. However, most studies have used traditional methods such as lectures, discussions, or printed materials. The use of game-based learning methods such as the Good Behavior Game (GBG) to improve knowledge about sexual violence has received limited attention, especially among junior high school students. Therefore, further research is needed to determine whether GBG is effective in increasing adolescents' knowledge about sexual violence. This study aims to determine the effect of the educational media GBG on the level of knowledge about sexual violence in adolescents. This study used a pre- experimental design with a one-group pretest–posttest approach. Ninety-one students in grades VII, VIII, and IX of SMP Negeri 9, Kediri City, were selected using a purposive sampling technique. The research instrument was a questionnaire on the level of knowledge about sexual violence. Data were analyzed descriptively and inferentially using the Wilcoxon Signed Ranks Test with a significance level of α = 0.05. The results showed that before the education, most respondents had a low level of knowledge about sexual violence (61.5%). After education using GBG, most respondents improved to a good level (93.4%). The Wilcoxon test showed a significant difference between the levels of knowledge before and after the intervention (p = 0.000 < 0.05). GBG educational media has been effective in increasing adolescents' knowledge about sexual violence because it uses an interactive, participatory, and group-based learning approach that can increase student engagement, attention, and understanding of the material more effectively than conventional educational methods.